Randomised benchmarking with gate-dependent noise : plus applications in the triple quantum dot qubit - Zaw, Lin Htoo (Nanyang Technological University, 2020)
Quantum computers promise a major speedup over their classical counterparts by taking advantage of quantum effects. However, this increased performance is hindered by the tendency of quantum computers to be considerably error-prone. Therefore, the identification and elimination of noise processes in quantum systems are needed before general purpose quantum computers can be practically useful. The study of noise characterisation methods is an important part of this effort towards fault tolerant computation.